ART THERAPY ON BULLYING-VICTIMS BEHAVIOR AGED 5-6 - Ndari, Susianty Selaras; Tasya, Fadilah (Journal of Early Childhood Education (JECE), 2021)
This study aims to examine the effectiveness of art therapy on the behavior of children aged 5-6 years who are victims of bullying. Single Subject Research with A-B-A design is the method used. The subject of this study was one early childhood who experienced psychological bullying. This study used a description test, observation, and documentation. The results show that A (1) and A (2) the overall average score of subjects (AL) in Baseline 1 (A1) conditions is 47, which is categorized as poor, on intervention baseline data, it gets 64.2, and after intervention baseline 2 (A2) of 69.3 so that during and after the intervention the results revealed that art therapy was quite good as an intervention for children who were victims of bullying. Thus, the effectiveness of therapy in children who experience bullying is successful. This study recommends using drawing activities to provide intervention against psychological problems in children who are victims of bullying.